Hair Loss: Pathogenesis and Prevention: A Literature Review - Sowińska, Teresa; Łabuda, Mikołaj; Słojewska , Aleksandra; Kotkowiak, Agata; Mentel, Oliwia; Bogucka , Adrianna; Szema, Agnieszka; Królikowska, Klaudia; Sikora , Jakub; Knychalska , Karolina (Quality in Sport, 2025)
Introduction and purpose: Hair loss, clinically referred to as alopecia, represents a significant dermatological challenge that impacts millions of people worldwide. This disorder can lead to significant psychosocial distress, affecting self-esteem and quality of life across different age groups and genders. Its multifactorial etiology involves genetic predispositions, hormonal imbalances, immune-mediated mechanisms, and environmental influences. This literature review focuses on the latest reports on the pathogenesis of hair loss and summarizes current strategies for its prevention. State of knowledge: Hair loss occurs when the normal hair growth cycle is disrupted, leading to premature shedding. Genetic predisposition, especially in androgenetic alopecia, increases follicle sensitivity to hormonal changes. Androgens shorten the growth phase and thin hair, while estrogen decline in women can worsen hair loss. Other hormones such as growth hormone, prolactin, melatonin, cortisol, and thyroid hormones also play key roles in hair maintenance. Stress elevates cortisol, which can push hair into its resting phase earlier than normal. Immune responses in conditions like alopecia areata result in the body attacking its own hair follicles. Environmental pollutants and nutritional deficiencies further compromise hair structure. Preventive measures- such as balanced nutrition, stress management, and topical treatments- can help maintain healthier hair. Conclusion: By deepening our understanding of the pathogenesis of hair loss, we can enhance our ability to diagnose the condition and identify its underlying causes. Given the diverse etiologies, each patient should be evaluated individually, with treatment tailored to the specific findings of their examination.